Efeitos da nitretação a plasma e do filme de carbono amorfo (a-C:H) aplicado ao aço 1020 na resistência ao desgaste em alumínio AA 3104 - Soares, Fábio (2020)
The AA 3104 aluminum is widely used as packaging for food storage, as it is a versatile alloy with easy mechanical conformation, however, it causes high wear to the cutting knife due to friction during the packaging operation. The objective of this study was to evaluate the wear resistance of steel containing 0.2% C, commonly applied to tools to perform forming and cutting operations on AA 3104 aluminum alloy, subjecting this steel to plasma ion nitriding and deposition treatments amorphous carbon film (a-C:H), to study the wear behavior of the material with and without surface treatment. The a-C:H films were deposited by PECVD on 1020 steel samples after cleaning the substrate by plasma ablation, with atmospheres of 80 and 90% CH4, with voltage varying between 500 and 600V. For the adhesion of a-C:H film to the metallic substrate, a silicon interface was deposited using hexamethyldisiloxane as a precursor, whose deposition was carried out with a gas flow of 30 sccm, containing 70% HMDSO and 30% argon. The plasma nitriding treatments were carried out with an atmosphere containing 80% N2 and 20% H2 with temperatures at 400, 500 and 600 °C. Also, plasma nitriding treatment was carried out where the temperature was maintained at 550 °C and the gas proportions were varied by 60% N2 and 40% H2, 80% N2 and 20% H2 and 92% N2 and 8% H2. All samples were subjected to the micro-wear test by fixed ball and the prototypes of the treated tools were tested using a wear machine specially built to simulate the friction between 1020 steel and AA 3104 aluminum. The final wear analysis was done through the optical moiré technique by phase-shifting that allowed to analyze both qualitatively and quantitatively the volume of body wear with and without treatment. Among the nitrided samples, those that were produced with higher nitrogen rates showed greater hardness due to the formation of the Fe2-3N phase, reaching values of 585 HV, however the samples with a low nitrogen atmosphere obtained Fe4N phase where they showed to be more resistant to frictional stresses due to its greater ductility in relation to the Fe2-3N phase, ensuring 60% less wear on untreated material. The a-C:H film produced with an atmosphere containing 80% CH4 showed a lower roughness among all samples (44.3 nm), leading to a lower wear volume (1.015x10-4 mm3). The a-C:H films gave steel 1020 results superior to nitriding, with a 95% reduction in wear volume. It was observed that all treated samples obtained an increase in wear resistance, when compared to the base material, thus making it possible to reduce the wear of the 1020 steel tools used for cutting aluminum AA 3104 and, subsequently, increasing its useful life.